Optimalisasi Proses Bisnis pada Digitalisasi untuk Meningkatkan Produktivitas UKM “Toolsku 3D Printing” - Prabaswari, Atyanti Dyah; Waskita, Farid Agung; Santoso, Dwi Wahyu; Sutrisno, Wahyudhi (Universitas Islam Indonesia, 2025)
UKM Toolsku 3D Printing is one of the creative business actors in Kalasan District, Yogyakarta that produces goods based on 3D printing technology according to consumer demand. Despite having good production capacity, partners face obstacles in optimizing digital product marketing, limited attractive packaging, and low consumer awareness of the brands they own. These problems cause stagnation in business growth and low absorption of filament production. To overcome these challenges, this community service activity was carried out using a design thinking approach, which consists of five stages: empathize, define, ideate, prototype, and test. Through a participatory approach, partners are actively involved in every stage from identifying problems, formulating solutions, to implementing business process digitalization strategies. The main activities include introducing the concept of MSME digitalization, training in implementing information technology-based work systems, mentoring in improving branding and product packaging designs, creating digital e-catalogs on e-commerce platforms, and digital marketing training through social media. The results of the activities showed a significant increase in partners' understanding of digital technology, strengthening brand identity, and increasing engagement and market reach through online platforms. This activity has succeeded in forming the foundation of a sustainable digital system that is responsive to market needs. In addition, partners have demonstrated continued initiatives such as the appointment of special staff for digital marketing, reflecting the sustainability of the interventions carried out. Thus, this activity not only increases the internal capacity of UKM Toolsku, but can also be used as a model for digital-based empowerment for other UKMs in the current era of digital transformation.